Hubungan Pola Asu Orang Tua dalam Pemberian Makana dengan Kejadian Stunting pada Anak Usia 24-59 Bulan - Erviana, Erviana; Widiani, Widiani; Taufik, Muhammad Taufik Page; Damayanti, Risna (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Stunting is a long-term nutritional problem in toddlers, characterized by a shorter height than other children of the same age. This study aims to determine the relationship between parenting styles in feeding and the incidence of stunting in children aged 24-59 months in North Bonde Village. This study uses a cross-sectional approach, a study that collects data on several research variables simultaneously. The sample in this study were 125 respondents. This research was conducted in North Bonde Village. The research instrument used was a questionnaire with 24 question items. The statistical test used is the mann-whitney test. The results of this study found that there was a relationship between parenting styles in feeding and the incidence of stunting in children aged 24-59 months in North Bonde village as evidenced by the value of ? (0.011) < ? (0.05). The conclusion of this study is that there is a relationship between parenting style in feeding and the incidence of stunting in children aged 24-59 months in Bonde Utara village, the type of parenting style in providing feeding and the incidence of stunting in children aged 24-59 months in North Bonde Village.